Las habilidades comunicativas, una necesidad formativa del profesional del Siglo XXI - Cevallos Mieles, Otto (2016)
Although governments and institutions from different countries have become aware of the need for change, higher education has shown the same shortages and challenges that were inherited in the first two decades of the century. In Ecuador, Many Changes in Education have begun in all universities and higher education institutions through new curriculum development in order to generate expectation in political, economic and social spheres. In this context, the formation of the jurist has involved a new look in their competences. The need to express themselves in public, manage human groups, argue, persuade, inform and convince, are the required skills to achieve communicative skill development. These must be the fundamental premise to develop competences that allow jurists to manage the verbal, nonverbal, and paralinguistic communication and their components effectively. It is important to consider that not only oral language skill is useful to convey messages and support the arguments used in speech and expositions. This paper focuses on the needs to master the knowledge and skills of nonverbal and paralinguistic aspects and their importance in communication. It is meant to provide a more effective guidance for the several situations a lawyer has to deal with in different areas of his/her performance.